IMPROVING STUDENTS’ READING COMPREHENSION BY USING MOBILE LEARNING MODEL AT UPT SPF SMP NEGERI 4 MAKASSAR - Lifana, Salwa; Muhsin, Muhammad Arief; Azis, Awalia (FKIP Unismuh Makassar, 2024)
The aims of this research was to find out the improvement of the student about reading comprehension after using Google Classroom media. This research conducted by used Quantitative method with CAR (Class Action Research). This research population consisted of eighth grade students at UPT SPF SMP Negeri 4 Makassar, with the research sample being Class VIII.8, which consisted of 30 Students, selected by purposive sampling technique. The data from this research gathered through the supply of diagnostic test, test 1 & test 2 to find out an improvement of students' reading comprehension after using Google Classroom as teaching/learning media.The result of this study was significant improvement in reading comprehension of students. This can be shown in the average value of the students of the D-test in the first cycle and the test in the second cycle. The average value of the first cycle test on the aspect of the main idea (94.33) was higher than the D-test (4.17). Then in the aspect of supporting ideas, the mean test cycle I (90.63) was higher than the D-test (26.13). The average test cycle II on aspects of the main idea (98.83) was higher than the first cycle (94.33). While the mean test cycle II in supporting aspects of the idea (93.37) was higher than the first cycle (90.63). The results showed that there was a significant increase in students ' reading comprehension skills after using Google Classroom as an English learning media